Postretrieval Microinjection of Baclofen Into the Agranular Insular Cortex Inhibits Morphine-Induced CPP by Disrupting Reconsolidation - Sun, Kuisheng; Mu, Qingchun; Chang, Haigang; Zhang, Chun; Wang, Yehua; Rong, Shikuo; Liu, Shenhai; Zuo, Di; He, Zhenquan; Wan, Ding; Yang, Hua; Wang, Feng; et al. (Frontiers in Pharmacology, 2020)
Environmental cues that are repeatedly experienced by individuals while on psychotropic drugs can both promote compulsive drug taking and craving and are a primary trigger of relapse, which has been considered to be one of representative characteristics of addiction. Consequently, attenuating the strength of cue-drug memories could reduce the number of factors that cause drug craving and relapse. Interestingly, impairing cue-drug memory reconsolidation is a generally accepted strategy aimed at reducing the intensity of cues that trigger drug-seeking and drug-taking behaviors. In addition, the agranular insular cortex (AI) is an important component of the neural circuits underlying drug-related memory reconsolidation. GABAB receptors (GABABRs) are potential targets for the treatment of addition, and baclofen (BLF) is a specific GABAB compound available for application in clinical addiction treatment. Furthermore, ΔFosB is considered a biomarker for the evaluation of potential therapeutic interventions for addiction. Here, we used the morphine-induced conditioned place preference (CPP) paradigm to investigate whether postretrieval microinjections of BLF into the AI could affect reconsolidation of drug-reward memory, reinstatement of CPP and the level of ΔFosB in mice. Our results showed that BLF infused into the AI after morphine CPP memory retrieval, but not under control conditions, could eliminate the expression of a morphine CPP memory. This effect persisted in a morphine-priming–induced reinstatement test, suggesting that baclofen in the AI was capable of preventing the reconsolidation of the morphine CPP memory. Our results also showed that these behavioral effects were associated with reduced morphine-associated ΔFosB expression. BLF-induced disruption of morphine memory reconsolidation also resulted in improved performance in a spatial learning and reversal learning task, suggesting that the loss of the morphine CPP memory also improved cognition. Taken together, our research supports that GABABRs in AI have an important role for drug-cue memory reconsolidation and increase our understanding of the role of the AI in drug-related learning and memory.